The Existence of Blind Radio Drama Represents the Real World - Adnan, Muhammad; Tantri, Niki Raga; Pribadi, Fantri; Astari, Andi Tenri Juli; Utama, Galuh Tulus (Fakultas Ilmu Budaya, Universitas Jambi, 2025)
Radio drama, as an auditory medium, is often perceived as